Skin cancer’s prevention in the light of current medical knowledge - Milanowska, Małgorzata; Grudzińska, Aleksandra; Jarosz, Dominika; Tsitko, Hanna; Dudzińska, Paulina (Journal of Education, Health and Sport, 2023)
Among all diagnosed malignancies, skin cancers account for more than 30-50%. Caucasian patients have a lifetime risk of more than 20%. The incidence increases with the age of patients. In 2017, there were over 14,000 new cases in Poland. It can be expected that these results are underestimated due to incomplete registration of new cases in the National Cancer Registry.(1,2)The most common skin cancer is basal cell carcinoma - over 80% of cases. In second place is squamous cell carcinoma - 15-20%. Other types are less common.(1)The appearance of a new mole or a change in the appearance of an existing one is often missed at the beginning, and even if it is noticed, it is underestimated by the patient. Therefore, detection rate of skin cancer, including melanoma at an early stage, is unfortunately relatively low.The incidence of skin cancer is constantly increasing, which is an important epidemiological problem of modern medicine.(2)Patient education should focus on behaviors that the patient can influence and modify, including: regular visits to a dermatologist and undergoing a dermatoscopic examination, the use of sunscreen with a high UV factor, the use of special protective clothing, sunglasses, covering head when under sun’s exposure, moderate overall sun exposure, avoiding sunburn, not using a tanning bed.The purpose of this review was to assess the current literature on the impact of educating the public and promoting sun protection as a necessary method to directly reduce the incidence of skin cancer.The literature was searched in Pubmed and Google Scholar databases.